Stapes footplate’s posterior border protrudes the vestibule in healthy ears: anatomical insights from ultra-high-resolution CT - Ruowei Tang; Ning Xu; Zhengyu Zhang; Zhongrui Chen; Heyu Ding; Zhenghan Yang; Zhenchang Wang; Pengfei Zhao (BMC Medical Imaging)
Abstract Background The stapes footplate (SF) and annular ligament (AL) in the oval window region are of paramount significances. This study aims to assess the visibility of AL and the relative positioning of the SF and vestibule using ultra-high-resolution computed tomography (U-HRCT). Methods U-HRCT images between September 2020 and April 2023 were retrospectively reviewed, and 479 ears deemed healthy from both clinical and radiological perspectives were included. AL was considered visible when manifesting as linear low attenuation between the SF and oval window, and the visibility was assessed for its four borders (anterior, posterior, superior and inferior). Two neuroradiologists conducted measurements independently for the SF length, SF-oval window angle, and SF protrusion depth into the vestibule. The results were described on the entire cohort, and compared by age and by sex. Results A cohort comprising 479 participants [median age 58 years (interquartile range 35–65); 269 females] with 479 healthy ears were included. The inferior border of the AL region demonstrated the highest visibility (476/479, 99.4%), whereas the posterior border exhibited the lowest visibility rate (394/479, 82.3%). The median protrusion depth of the SF posterior border into the vestibule was 0.4 mm (interquartile range 0.3–0.5 mm). Statistically significant differences were observed within age and sex groups for the SF length and the SF protrusion depth (all P < 0.05). Conclusions This study established radiological features for the SF and AL in healthy ears through U-HRCT. The findings are essential for providing normative references, expediting disease diagnosis, and aiding in selection of surgical strategy. Trial registration Retrospectively registered.